Pengembangan kapasitas organisasi melalui penerapan agile management pada CV Nurillah Safety Semarang - Rizky Ghoffar Ismail; Sri Suwitri; Randi Randi; Arrahman Syafebri (STAI Auliaurrasyidin Tembilahan, 2026)
Rapid changes in the business environment require organizations to maintain high adaptability; however, many small and medium-sized enterprises still rely on bureaucratic work patterns that hinder decision-making speed. This Community Service (PkM) activity aimed to enhance the organizational capacity of CV. Nurillah Safety Semarang through the implementation of Agile Management. The program emphasized conceptual understanding, training in Agile tools (Scrum, Kanban, and Sprint Planning), and implementation support. Conducted on December 9, 2025, the activity applied methods including needs assessment, workshops, practical exercises, and evaluation. The results indicated a 50% increase in participants’ understanding of Agile concepts based on pre–post test measurements. Furthermore, improvements were observed in internal team communication, along with the initial adoption of Kanban boards for daily work visualization. These findings demonstrate that Agile Management is effective in strengthening adaptability and improving operational responsiveness in small organizations.